2015
DOI: 10.1007/s00330-015-3656-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Model-Based Iterative Reconstruction (MBIR) in reduced-dose CT for routine follow-up of patients with malignant lymphoma: dose savings, image quality and phantom study

Abstract: • In lymphoma patients, CT dose reduction is a major concern. • Reduced-dose body CT provides a fourfold radiation dose reduction. • Optimized CT reconstruction techniques (MBIR) can maintain image quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…As previously reported (6)(7)(8)(9)13,14,16,18,19,(21)(22)(23)(26)(27)(28)(29), IR algorithms enable a lower radiation dose for body CT acquisitions while preserving image quality. An evaluation of the 50% dose CT protocol by our four readers confirmed these findings, as diagnostic confidence was maintained and the subjective image quality of the reduced-dose images was still above average when compared to the reference, 100% dose images.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…As previously reported (6)(7)(8)(9)13,14,16,18,19,(21)(22)(23)(26)(27)(28)(29), IR algorithms enable a lower radiation dose for body CT acquisitions while preserving image quality. An evaluation of the 50% dose CT protocol by our four readers confirmed these findings, as diagnostic confidence was maintained and the subjective image quality of the reduced-dose images was still above average when compared to the reference, 100% dose images.…”
Section: Discussionmentioning
confidence: 60%
“…The potential for dose reduction using IR while preserving image quality has already been the subject of several publications (8,11,(13)(14)(15)(16)(17), but only a few studies have analyzed both chest and abdominal CT images (10,(18)(19)(20)(21)(22)(23)(24) and none have focused on young patients. As young patients represent the most radiosensitive population (25), they most urgently require an optimized radiation exposure, especially when they frequently undergo CT examinations, such as for follow-up of oncological disease.…”
Section: Introductionmentioning
confidence: 99%
“…For example, FBP has been found to have inferior image quality as compared to both MBIR and hybrid iterative reconstruction (HIR) and that MBIR yielded superior image quality to HIR for the cross‐sectional view . A study conducted by Hèrin et al concluded that MBIR reconstructions of reduced‐dose CT and FBP reconstruction of standard‐dose CT both obtained the same low contrast detectability on a phantom . This suggests that model‐based iterative reconstruction methods have the potential to perform better than FBP in terms of overall image quality and thus may impact Radiation Oncology‐related tasks.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 However, many technologic advances in CT techniques, such as iterative reconstruction, have been demonstrated to markedly improve the performance of low-dose CT acquisition. 23,24 Additionally, lowering tube voltage enhances the contrast attenuation in target vessels, thus maintaining a diagnostic CNR. As observed in our study, the mean image noise of the 80-kVp CTA protocol was statistically higher than that of the 120-kVp protocol; however, the image quality of the 80-kVp CTA protocol did not decrease despite the increase in noise.…”
Section: Discussionmentioning
confidence: 99%